Uma Peculiar Tafocenose Controlada por Ação Biogênica no Triássico Médio do Rio Grande do Sul, Brasil - DIAS, PAULA CAMBOIM DENTZIEN; SOARES, MARINA BENTO; MACHADO, CRISTINA BERTONI; KISLOWSKI, FELIPE FLACH (Pesquisas em Geociências, 2008)
We present here an outcrop with a peculiar fossil assemblage, including a distinct taphocoenosis in comparison to other fossiliferous outcrops of the Santa Maria Formation (Triassic, Paraná Basin). Fossil concentration in this outcrop is made-up of herbivorous non-mammalian cynodonts (Synapsida, Therapsida) only, tentatively assigned to Massetognathus. The taphocoenosis is characterized by the accumulation of bones within a restricted area, with predominance of skull and mandible remains, almost always disarticulated. Bones are mainly disarticulated and chaotically oriented in a massive, red-colored, muddy matrix. Both the nature of rock matrix and the absence of azimuthal orientation of the bones in the taphocoenosis indicated that tractive currents were not the main process responsible by the accumulation of those fossil remains, mainly skull and lower jaws bones. These are considered the less nutritious bone parts of the vertebrate skeleton and according to this, the skulls and lower jaws were left behind by selective scavengers that removed the more nutritious parts. So, this taphonomic model of preservation led us to the hypothesis of a biogenic concentration for this taphocoenosis based upon at the interpretation of this outcrop as a site of concentration of bones by selective scavengers.